Format and content of the safety analysis report for nuclear power plants : specific safety guide. (Safety standards series, 2021)
"This Safety Guide provides recommendations on the structure and content of the safety analysis report to be submitted by the operating organization to the regulatory body for authorization of the siting, construction, commissioning, operation and decommissioning of a nuclear power plant. It is intended to facilitate both the development of the safety analysis report by the operating organization and the checking of its completeness and adequacy by the regulatory body. The publication is a revision of IAEA Safety Standards Series No. GS-G-4.1, Format and Content of the Safety Analysis Report for Nuclear Power Plants, which it supersedes. The revision reflects feedback experience from the Fukushima Daiichi accident and the subsequent stress tests performed. It also describes good practices and experience from the use of safety analysis reports for newly built nuclear power plants in different States and informs on recent progress made in approaches to safety assessment."--Publisher's description.